Development of and Recovery from Secondary Hypogonadism in Aging Men: Prospective Results from the EMAS - Rastrelli, Giulia; Carter, Emma L.; Ahern, Tomas; Finn, Joseph D.; Antonio, Leen; O'Neill, Terence W.; Bartfai, Gyorgy; Casanueva, Felipe F.; Forti, Gianni; Keevil, Brian; Maggi, Mario; Giwercman, Aleksander; et al. (The journal of clinical endocrinology and metabolism, 2015)
Context:Secondary hypogonadism is common in aging men; its natural history and predisposing factors are unclear.Objectives:The objectives were 1) to identify factors that predispose eugonadal men (T ≥ 10.5 nmol/L) to develop biochemical secondary hypogonadism (T < 10.5 nmol/L; LH ≤ 9.4 U/L) and secondary hypogonadal men to recover to eugonadism; and 2) to characterize clinical features associated with these transitions.Design:The study was designed as a prospective observational general population cohort survey.Setting:The setting was clinical research centers.Participants:The participants were 3369 community-dwelling men aged 40–79 years in eight European centers.Intervention:Interventions included observational follow-up of 4.3 years.Main Outcome Measure:Subjects were categorized according to change/no change in biochemical gonadal status during follow-up as follows: persistent eugonadal (n = 1909), incident secondary hypogonadal (n = 140), persistent secondary hypogonadal (n = 123), and recovered from secondary hypogonadism to eugonadism (n = 96). Baseline predictors and changes in clinical features associated with incident secondary hypogonadism and recovery from secondary hypogonadism were analyzed by regression models.Results:The incidence of secondary hypogonadism was 155.9/10 000/year, whereas 42.9% of men with secondary hypogonadism recovered to eugonadism. Incident secondary hypogonadism was predicted by obesity (body mass index ≥ 30 kg/m2; odds ratio [OR] = 2.86 [95% confidence interval, 1.67; 4.90]; P < .0001), weight gain (OR = 1.79 [1.15; 2.80]; P = .011), and increased waist circumference (OR = 1.73 [1.07; 2.81], P = .026; and OR = 2.64 [1.66; 4.21], P < .0001, for waist circumference 94–102 and ≥102 cm, respectively). Incident secondary hypogonadal men experienced new/worsening sexual symptoms (low libido, erectile dysfunction, and infrequent spontaneous erections). Recovery from secondary hypogonadism was predicted by nonobesity (OR = 2.28 [1.21; 4.31]; P = .011), weight loss (OR = 2.24 [1.04; 4.85]; P = .042), normal waist circumference (OR = 1.93 [1.01; 3.70]; P = .048), younger age (< 60 y; OR = 2.32 [1.12; 4.82]; P = .024), and higher education (OR = 2.11 [1.05; 4.26]; P = .037), but symptoms did not show significant concurrent improvement.Conclusion:Obesity-related metabolic and lifestyle factors predispose older men to the development of secondary hypogonadism, which is frequently reversible with weight loss.